Simple additive effects are rare: a quantitative review of plant biomass and soil process responses to combined manipulations of CO 2 and temperature - Wouter I. J. Dieleman; Sara Vicca; Feike A. Dijkstra; Frank Hagedorn; Mark J. Hovenden; Klaus S. Larsen; Jack A. Morgan; Astrid Volder; Claus Beier; Jeffrey S. Dukes; John King; Sebastian Leuzinger; et al. (Global Change Biology, 2012)
In recent years, increased awareness of the potential interactions between rising atmospheric CO 2 concentrations ([ CO 2 ]) and temperature has illustrated the importance of multifactorial ecosystem manipulation experiments for validating Earth System models. To address the urgent need for increased understanding of responses in multifactorial experiments, this article synthesizes how ecosystem productivity and soil processes respond to combined warming and [ CO 2 ] manipulation, and compares it with those obtained in single factor [ CO 2 ] and temperature manipulation experiments. Across all combined elevated [ CO 2 ] and warming experiments, biomass production and soil respiration were typically enhanced. Responses to the combined treatment were more similar to those in the [ CO 2 ]‐only treatment than to those in the warming‐only treatment. In contrast to warming‐only experiments, both the combined and the [ CO 2 ]‐only treatments elicited larger stimulation of fine root biomass than of aboveground biomass, consistently stimulated soil respiration, and decreased foliar nitrogen (N) concentration. Nonetheless, mineral N availability declined less in the combined treatment than in the [ CO 2 ]‐only treatment, possibly due to the warming‐induced acceleration of decomposition, implying that progressive nitrogen limitation ( PNL ) may not occur as commonly as anticipated from single factor [ CO 2 ] treatment studies. Responses of total plant biomass, especially of aboveground biomass, revealed antagonistic interactions between elevated [ CO 2 ] and warming, i.e. the response to the combined treatment was usually less‐than‐additive. This implies that productivity projections might be overestimated when models are parameterized based on single factor responses. Our results highlight the need for more (and especially more long‐term) multifactor manipulation experiments. Because single factor CO 2 responses often dominated over warming responses in the combined treatments, our results also suggest that projected responses to future global warming in Earth System models should not be parameterized using single factor warming experiments.

Elevated CO 2 affects photosynthetic responses in canopy pine and subcanopy deciduous trees over 10 years: a synthesis from D uke FACE - David S. Ellsworth; Richard Thomas; Kristine Y. Crous; Sari Palmroth; Eric Ward; Chris Maier; Evan DeLucia; Ram Oren (Global Change Biology, 2012)
Leaf responses to elevated atmospheric CO 2 concentration (C a ) are central to models of forest CO 2 exchange with the atmosphere and constrain the magnitude of the future carbon sink. Estimating the magnitude of primary productivity enhancement of forests in elevated C a requires an understanding of how photosynthesis is regulated by diffusional and biochemical components and up‐scaled to entire canopies. To test the sensitivity of leaf photosynthesis and stomatal conductance to elevated C a in time and space, we compiled a comprehensive dataset measured over 10 years for a temperate pine forest of P inus taeda , but also including deciduous species, primarily L iquidambar styraciflua . We combined over one thousand controlled‐response curves of photosynthesis as a function of environmental drivers (light, air C a and temperature) measured at canopy heights up to 20 m over 11 years (1996–2006) to generate parameterizations for leaf‐scale models for the D uke free‐air CO 2 enrichment ( FACE ) experiment. The enhancement of leaf net photosynthesis ( A net ) in P . taeda by elevated C a of +200 μmol mol −1 was 67% for current‐year needles in the upper crown in summer conditions over 10 years. Photosynthetic enhancement of P . taeda at the leaf‐scale increased by two‐fold from the driest to wettest growing seasons. Current‐year pine foliage A net was sensitive to temporal variation, whereas previous‐year foliage A net was less responsive and overall showed less enhancement (+30%). Photosynthetic downregulation in overwintering upper canopy pine needles was small at average leaf N ( N area ), but statistically significant. In contrast, co‐dominant and subcanopy L . styraciflua trees showed A net enhancement of 62% and no A net – N area adjustments. Various understory deciduous tree species showed an average A net enhancement of 42%. Differences in photosynthetic responses between overwintering pine needles and subcanopy deciduous leaves suggest that increased C a has the potential to enhance the mixed‐species composition of planted pine stands and, by extension, naturally regenerating pine‐dominated stands.